Stock exchange alliances, access fees and competition - Oz Shy; Juha Tarkka (Bank of Finland, 2001)
This paper investigates the market consequences of alliance formation among stock exchanges.These alliances enable brokers to match investors internationally at their local market, thereby eliminating the need for brokers to maintain memberships in foreign stock exchanges.We sort out the conditions under which alliance formation increases profits for stock exchanges and brokers, and how changes in fee structures affect investors' participation rates and welfare.Finally, we examine several methods for implementing access fees and their welfare implications.
URN:NBN:fi:bof-20140807608
Keywords: 330; stock exchange alliances; access fees; competition among stock exchanges